Primitive meteorites and asteroids : physical, chemical, and spectroscopic observations paving the way to exploration - Abreu Zambrano, Neyda Margarita (Elsevier, 2018)
Primitive Meteorites and Asteroids: Physical, Chemical, and Spectroscopic Observations Paving the Way to Exploration covers the physical, chemical and spectroscopic aspects of asteroids, providing important data and research on carbonaceous chondrites and primitive meteorites. This information is crucial to the success of missions to parent bodies, thus contributing to an understanding of the early solar system. The book offers an interdisciplinary perspective relevant to many fields of planetary science, as well as cosmochemistry, planetary astronomy, astrobiology, geology and space engineering. Including contributions from planetary and missions scientists worldwide, the book collects the fundamental knowledge and cutting-edge research on carbonaceous chondrites and their parent bodies into one accessible resource, thus contributing to the future of space exploration.